High abilities / giftedness in higher education: An analysis of Brazilian theses and dissertations - de Oliveira, Ana Paula [UNESP]; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Capellini, Vera Lucia Messias Fialho [UNESP] (FapUNIFESP (SciELO), 2020)
The aim of this study was to review Brazilian dissertations and theses on High Ability / Giftedness (HA / G) in higher education. For this, we searched the Brazilian Digital Library of Theses and Dissertations. The theses and dissertations were categorized according to the frequency of publication over the years, the universities of origin, the type of study, the objectives, the number of participants and the main results. Forty-seven researches were found and, from reading the abstracts, those that did not specifically address the issue of HA / G in the university context and / or that were repeated were excluded, resulting in a total of seven, five of which were master's and two doctoral degrees between 2011 and 2017. It was concluded that the topics most addressed in the research related to identification. It is a topic of recent interest and lacking studies that investigate broader issues related to college students with HA/ G.
Keywords: Higher education; Intellectual giftedness; Literature review